Kidney size estimation in Korean children with Technesium-99m dimercaptosuccinic acid scintigraphy - Lee, Min Jung (The Korean Pediatric Society, 2014)
PURPOSE: Renal size is an important indicator to determine adequate organ growth in children. The aim of this study was to estimate renal size with Technesium-99m dimercaptosuccinic acid (DMSA) scan and propose a simple formula for predicting renal length in normal Korean children. METHODS: This study included 346 children (148 boys and 198 girls; age range, 1 month to 17 years) in whom renal length was measured using the DMSA scan. Patients with anatomical renal abnormalities or acute pyelonephritis were excluded. Children were divided into two groups: 214 children (61.8%) were less than a year old (group 1) and 132 (38.2%) were ≥1 year (group 2). RESULTS: Renal length was larger on the left side than the right side, and there was no significant gender-related difference in renal length. We propose the following formula for renal length based on the analysis of the 346 children in our study: the formula was as follows: 4.682×age (month)(0.137), R(2)=0.780. In group 1, the formula was renal length (cm)=0.127×age (month)+5.144, R(2)=0.354, and in group 2, the formula was 0.334×age (year)+6.477, R(2)=0.829. CONCLUSION: It is difficult to establish simple formulae in infants (R(2)=0.354). Therefore, further studies including relevant variables are needed for this age group. We proposed formulae to estimate renal length in Korean children over 1 year of age by using the DMSA scan.